Analisis Hak Serta Rehabilitasi Nama Baik Korban Tindak Pidana Pencemaran Nama Baik Melalui Media Sosial - Jekson Kipli Lumban Toruan; Jinner Sidauruk (Perspektif Administrasi Publik dan hukum, 2025)
The rapid development of globalization today facilitates access to information circulating on social media, both positive and negative. This study examines the increasing cases of defamation in the digital age, focusing on legal protection aspects and rehabilitation efforts for victims. The purpose of this writing is to understand the role of the government and law enforcement authorities in addressing defamation offenses. Using a normative legal research method, it is concluded that: 1. To understand the forms of defamation offenses, 2. To determine the rights of victims of defamation. Protection and rehabilitation efforts for one's reputation are crucial in this era, considering the advancements in technology and the widespread occurrence of defamation.